Motor neuron diseases caused by a novel VRK1 variant – A genotype/phenotype study. Issue 11 (27th September 2019) - Sedghi, Maryam; Moslemi, Ali‐Reza; Olive, Montse; Etemadifar, Masoud; Ansari, Behnaz; Nasiri, Jafar; Emrahi, Leila; Mianesaz, Hamid‐Reza; Laing, Nigel G.; Tajsharghi, Homa
Abstract: Background: Motor neuron disorders involving upper and lower neurons are a genetically and clinically heterogenous group of rare neuromuscular disorders with overlap among spinal muscular atrophies (SMAs) and amyotrophic lateral sclerosis (ALS). Classical SMA caused by recessive mutations in SMN1 is one of the most common genetic causes of mortality in infants. It is characterized by degeneration of anterior horn cells in the spinal cord, leading to progressive muscle weakness and atrophy. Non‐SMN1‐related spinal muscular atrophies are caused by variants in a number of genes, including VRK1, encoding the vaccinia‐related kinase 1 (VRK1). VRK1 variants have been segregated with motor neuron diseases including SMA phenotypes or hereditary complex motor and sensory axonal neuropathy (HMSN), with or without pontocerebellar hypoplasia or microcephaly. Results: Here, we report an association of a novel homozygous splice variant in VRK1 (c.1159 + 1G>A) with childhood‐onset SMA or juvenile lower motor disease with brisk tendon reflexes without pontocerebellar hypoplasia and normal intellectual ability in a family with five affected individuals. We show that the VRK1 splice variant in patients causes decreased splicing efficiency and a mRNA frameshift that escapes the nonsense‐mediated decay machinery and results in a premature termination codon. Conclusions: Our findings unveil the impact of the variant on the VRK1 transcript and further support the implication of VRK1 in the pathogenesis of lower motor neuron diseases.